Biochemical and organoleptic changes of surimi from the Thai pangas (Pangasianodon hypophthalmus) during frozen storage - Majumdar, Ranendra Kumar; Debbarma, Sujata (Indian Journal of Fisheries, 2013)
A study was conducted on the feasibility of preparing myofi brillar protein concentrate (surimi) from the catfi sh, Pangasianodon hypophthalmus with specifi c aim to assess shelf life of washed mince at −20°C based on the changes in biochemical and functional qualities. The moisture and pH increased signifi cantly in the washed mince. The ash, total lipid and crude protein contents were higher in the unwashed mince, whereas, there was a positive effect on fi sh quality according to marked content decrease in expressible moisture, volatile basic amines, free fatty acids and thiobarbituric acid reactive substances. During storage of washed mince for 90 days at −20°C, moisture, ash, protein, fat and non-protein nitrogen contents registered decrease, whereas functional attributes of the surimi such as salt soluble protein, water holding capacity and gel strength were found to decrease during this period. While the appearance and odour of the product was acceptable throughout the storage period, the texture of the surimi was found in the border line on day 90. Based on these, the functional shelf life of washed pangas mince under frozen storage condition was estimated to be 90 days.